Comparison of Student Learning Outcomes in Middle School Science Classes with an STS Approach and a Typical Textbook Dominated Approach - (:unkn) unknown (Routledge, 2008)
The purpose of this study was to determine whether Science, Technology, and Society (STS) learning increases student concept mastery, general science achievement, use of concepts in new situations, and attitudes toward science in middle school classrooms. The study involved two teachers and fifty-two students in grades 6 through 8. Two sections of middle school science were taught by two longtime teachers where one used an STS approach and the other retained a typical use of the textbook as a class organizer. Each teacher administered the same pre- and post-assessments. Major findings indicated that middle school students experiencing the STS format with constructivist teaching practices: (1) learned basic concepts as well as students who studied them directly from the textbook, (2) achieved as much general concept mastery as students who studied in a textbook dominated way, (3) applied science concepts in new situations better than students who studied science in a more traditional way, (4) developed more positive attitudes about science, (5) exhibited creativity skills that were more individual and occurred more often, and (6) learned and used science at home and in the community more than students in the typical textbook dominated section. Further, the STS approach coincided well with the kind of teaching across the curriculum that is (recommended as) central to teaching in middle schools. © 2008, © 2008 National Middle School Association.